Identification of DAPK1 as an autophagy-related biomarker for myotonic dystrophy type 1 - Hu, Min; Ge, Meng-Ru; Li, Hong-Xia; Zhang, Bei; Li, Gang (Frontiers in Genetics, 2022)
Myotonic dystrophy type I (DM1), a CTG repeat expansion hereditary disorder, is primarily characterized by myotonia. Several studies have reported that abnormal autophagy pathway has a close relationship with DM1. However, the underlying key regulatory molecules dictating autophagy disturbance still remains elusive. Previous studies mainly focused on finding targeted therapies for DM1, but the clinical heterogeneity of the DM1 is rarely addressed. Herein, to identify potential regulator genes related to autophagy, we performed weighted gene co-expression network analysis (WGCNA) to construct the co-expression network and screened out 7 core autophagy-related genes (DAPK1, TGFB2, SESN3, ATF4, MEG3, and COL1A1) by overlapping within differentially expressed genes (DEG), cytoHubba, gene significance (GS) and module membership (MM) score. Meanwhile, we here analyzed autophagy-related molecular subtypes of DM1 in relation to the clinical phenotype. Our results show that four genes (DAPK1, TGFB2, SESN3, and MEG3) contribute to distinguish these two molecular subtypes of DM1. We then develop an analysis of RNA-seq data from six human skin fibroblasts (3 DM1, 3 healthy donors). Intriguingly, of the 7 hallmark genes obtained, DAPK1 is the only confirmed gene, and finally identified in vitro by RT-PCR. Furthermore, we assessed the DAPK1 accuracy diagnosis of DM1 by plotting a ROC curve (AUC = 0.965). Our study identified and validated DAPK1 serve as a novel autophagy-related biomarker that correlate with the progression and management of DM1.